2019
DOI: 10.1111/age.12760
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study identifies variants in theCAPN9gene associated with umbilical hernia in pigs

Abstract: Pig umbilical hernia (UH) affects pig welfare and brings considerable economic loss to the pig industry. To date, the molecular mechanisms underlying pig UH are still poorly understood. To identify potential loci for susceptibility to this disease, we performed a genome-wide association study in an Erhualian 9 Shaziling F 2 intercross population. A total of 45 animals were genotyped using Illumina Porcine SNP60 BeadChips. We observed a SNP (rs80993347) located in the calpain-9 (CAPN9) gene on Sus scrofa chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Several quantitative trait loci (QTL) associated with UH have already been reported for pigs. In a search in the pig QTLdb (https://www.animalgenome.org/cgi-bin/QTLdb/SS/index -11/02/2019), 54 QTLs for umbilical hernia have been found in several pig breeds, being located in chromosomes SSC1, SSC2, SSC3, SSC4, SSC6, SSC7, SSC8, SSC9, SSC10, SSC11, SSC13, SSC14, SSC15, SSC16 and SSC17 [11][12][13][14]. Ding et al (2009) [11] performed the first genomic study with UH and found some chromosomic regions related to the appearance of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Several quantitative trait loci (QTL) associated with UH have already been reported for pigs. In a search in the pig QTLdb (https://www.animalgenome.org/cgi-bin/QTLdb/SS/index -11/02/2019), 54 QTLs for umbilical hernia have been found in several pig breeds, being located in chromosomes SSC1, SSC2, SSC3, SSC4, SSC6, SSC7, SSC8, SSC9, SSC10, SSC11, SSC13, SSC14, SSC15, SSC16 and SSC17 [11][12][13][14]. Ding et al (2009) [11] performed the first genomic study with UH and found some chromosomic regions related to the appearance of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies investigating genes involved with the occurrence of hernias have been performed using candidate genes and GWAS approaches [11,25,29,31,32,[57][58][59][60]. More recently, functional candidate genes were prospected for scrotal [6] and umbilical [7] hernias by our group using RNA-Seq approach.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic regions indicated in previous publications were analyzed using polymerase chain reaction: (1) fragment (chr14:59603379-59604090) containing single SNP (rs321865883) in exon 10 of CAPN9 (Li et al, 2019);…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…The encoded proteins belong to the interleukin‐6 family, which plays a role in cell differentiation, growth promotion, and inflammatory response to injury (Grindflek et al, 2018). A subsequent GWAS performed in an Erhualian × Shaziling F2 intercross population indicated a candidate SNP synonymous variant in the calpain‐9 ( CAPN9 ) gene, which is also located in SSC14 (Li et al, 2019). In a recent study of hernias in the Landrace breed, performed using RNA sequencing, a candidate SNP was described in the integrin α M ( ITGAM ) gene, which is involved in ectodermal cell differentiation (Rodrigues et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation